ASSESSMENT OF MANDIBULAR FRACTURE HEALING WITH RESORBABLE PLATES AND SCREWS; AN INTERVENTIONAL STUDY IN A TERTIARY CARE HOSPITAL - Quratul Ain; Arsalan Wahid; Tariq Javed (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVE: To determine the outcome of fracture healing using resorbable plates and screws in case of mandibular fracture in adults. STUDY DESIGN: Cohort Study SETTING: Department of Oral and Maxillofacial Surgery, Nishtar Institute of Dentistry, Multan. STUDY DURATION: th th Eight months (15 September 2010 to 14 May 2011) Subjects & Methods: Total 73 cases presented in Outpatient Department of Nishtar Institute of Dentistry Multan were diagnosed clinically on the basis of step deformity, mobility at fracture site, disturbed occlusion and swelling. Radiographs (OPG, PA view of face) were taken wherever required to conﬁrm step deformity and radiolucent or radiopaque line at fracture site. A detailed history of all the patients was taken including the etiology, followed by a clinical and radiographic examination. Patients were then treated with resorbable plates and screws. After six weeks ﬁnal assessment regarding infection, occlusion and mobility at the fracture site was made by consultant maxillofacial surgeon. RESULTS: Sample size of the study was 73 patients (n=73) and male to female ratio was 6.3:1. The mean age of the patients was 21.1±2.9 years. The age range was 16–25 years. Majority of the patients 37(50.7%) were between 21–25 years of age. Regarding the etiology, road trafﬁc accident was the major cause which was evident in 62 patients (84.9%) followed by interpersonal violence in 8 patients (11%). Regarding the site of fracture, 32 patients (43.8%) had parasymphyseal and 10 (13.7%) had symphyseal fracture of mandible. 8 cases (11%) had fracture of mandible body and 23(31.5%) had mandible angle fracture. The follow up visit after six weeks showed normal occlusion in 65 patients (89%), no infection in 71 patients (97.3%) and no mobility in 65 patients (89.0%). Outcome of treatment showed 64 patients (87.7%) with healed fracture while in 9 patients (12.3%) fracture did not heal. CONCLUSION: Fixation of mandibular fracture with resorbable plates and screws seems to be a good technique for mandibular fractures except cost of treatment.